Houses of Horror or Magical Kingdoms? Past Times Revisited with Miguel Ángel Asturias, Carlos Fuentes and Julio Cortázar - Lois Marie Jaeck (Ciencia Ergo Sum)
In the three short stories to be examined, Miguel Ángel Asturias, Carlos Fuentes and Julio Cortázar incorporate Pre-Columbian beliefs and customs into colonial and post-colonial Latin American reality. Their fictional mergers of past and present insinuate the reversibility/ambiguity of dreams/representation with physical reality. They thus recognize the authentic presence of Pre-Columbian culture in contemporary Latin American societies and put into question the validity of European/North American materialism.